Compounds detection and inhibition activity of chloroform and ethyl acetate extracts of Schizophyllum commune on some cancer cell types - Nuraeni Ekowati; ARIS MUMPUNI; NUNIEK INA RATNANINGTYAS; ARDHINI RIN MAHARNING (Society for Indonesian Biodiversity, 2020)
Abstract. Ekowati N, Mumpuni A, Ratnaningtyas NI, Maharning A. 2020. Compounds detection and inhibition activity of chloroform and ethyl acetate extracts of Schizophyllum commune on some cancer cell types. Biodiversitas 21: 5865-5871. Schizophyllum commune Fr.is a potential fungus utilized as a drug, including a cancer drug expectant. In Indonesia, the fungus' capability to suppress the growth of certain types of cancer cells has not been widely reported. The purposes of this study were (i) to determine the bioactive compound group from S. commune using organic solvents chloroform and ethyl acetate, (ii) to determine the IC50 values ??of S. commune bioactive compounds using cancer cell lines HeLa, MCF7, T47D and WiDr, (iii) to find out the mechanism of apoptosis. The research was carried out experimentally using a pure culture of four types of cancer cell lines. Anticancer activity test was conducted by a cytotoxic test using MTT [3- (4,5- dimethylthiazol -2-yl) -2.5-diphenyl tetrazolium bromide], and apoptosis test. Data analysis was performed with linear regression analysis, and the apoptosis test was analyzed descriptively. The results showed that the bioactive compounds produced by S. commune are alkaloids, terpenoids, and flavonoids. S. commune bioactive compounds potentially inhibit the four cancer cell lines used with IC50 values ??ranging from 5.44 to 420.48 ug/mL. Best result was obtained from S. commune extract of chloroform in T47D cells with IC50 = 5.44 ug/mL and are able to induce apoptosis.